Integrated Bioinformatics Analysis and Transcriptomics Analysis Predict Jumonji and AT Rich Interacting Domain2 (JARID2) as a Therapeutic Target in Human Cancers - Sreeshma, Bhuvanadas; Mohideen, Habeeb Shaik; Devi, Arikketh (International Journal of Experimental Research and Review, 2024)
Jumonji and AT Rich Interacting Domain2 (JARID2) protein is recognized as a pivotal gene among the Polycomb Repressive Complex2 (PRC2) components. Nevertheless, the systematic assessment of JARID2 in cancers will enable us to understand its possible role and mechanism. Therefore, in this study, a pan-cancer analysis of JARID2 in cancers using The Cancer Genome Atlas (TCGA) database was performed. We observed an increased expression of JARID2 mRNA and protein in multiple cancer tissues in comparison to the control. In addition, we showed that the high JARID2 expression was closely associated to the poor overall survival and disease-free survival rate of cancer patients. Moreover, upregulated JARID2 has been observed to be involved in triggering the tumor immune response. To supplement the findings, a differential expression profiling was performed using datasets of RNA-Seq of OSCC tissues, which were obtained from NCBI SRA database. In line with the previous findings, JARID2 was observed to be upregulated in OSCC tissues. The expression pattern was validated in various cancer cell lines using qRT-PCR analysis. Altogether, this study comprehensively demonstrates JARID2 as a possible oncogene in human cancer.